Allergenicity and oral tolerance of enzymatic cross-linked tropomyosin evaluated using cell and mouse models - Liu, Guang-Yu; Hu, Meng-Jun; Sun, Le-Chang; Han, Xin-Yu; Liu, Qing-Mei; Alcocer, Marcos J.C.; Fei, Dan-Xia; Cao, Min-Jie; Liu, Guang-Ming (American Chemical Society, 2017)
The enzymatic cross-linking of proteins to form high-molecular-weight compounds may alter their sensitization potential. The IgG-/IgE-binding activity, digestibility, allergenicity, and oral tolerance of cross-linked tropomyosin with tyrosinase (CTC) or horseradish peroxidase (CHP) were investigated. ELISA results demonstrated CTC or CHP reduced its IgE-binding activity by 34.5 ± 1.8 and 63.5 ± 0.6%, respectively. Compared with native tropomyosin or CTC, CHP was more easily digested into small fragments; CHP decreased the degranulation of RBL-2H3 cells and increased endocytosis by dendritic cells. CHP can induce oral tolerance and reduce allergenicity in mice by decreasing IgE and IgG1 levels in serum, the production of T-cell cytokines, and the percentage composition of dendritic cells. These findings demonstrate CHP has more potential of reducing the allergenicity than CTC via influencing the morphology of protein, changing the original method of antigen presentation, modulating the Th1/Th2 immunobalance, and inducing the oral tolerance of the allergen tropomyosin.